Evaluation of Cloud Storage Services Using PIECES Method - Ratna A. I. Wulandari; Johan J. C. Tambotoh (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Cloud Computing has become increasingly popular in this technological era. Cloud computing offers various services, including cloud storage to store data. Accordingly, this study seeks to evaluate cloud storage services using the PIECES method. The PIECES method is used mainly for the Performance, Data and Information, Control and Security, Efficiency, and Service variables. This research employs a quantitative approach by relying on the survey technique to generate data and the Structural Equation Modeling (SEM) to analyze the data. The results demonstrate that 6 (six) hypotheses are empirically supported, and 1 (one) is not supported. In particular, the hypothesis that predicts Control and Security affect Service exhibits a coefficient of 0.233 (t-statistic <1.96).